Analysis of the Influence of Accounting Implementation and Financial Literacy on Financial Management in MSMEs in Cirebon City - Davind Ervian Rafiandra; Syahara Magfirotul Aulia; Yudi Mahadianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of accounting implementation and financial literacy on financial management among Micro, Small, and Medium Enterprises (MSMEs) in Cirebon City. MSMEs are key contributors to the Indonesian economy, yet many still struggle with financial management due to poor accounting practices and low levels of financial literacy. This quantitative research involved 113 MSME actors as respondents, selected using Slovin's formula. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that both accounting implementation and financial literacy have a significant and positive influence on MSMEs’ financial management, either partially or simultaneously. Among these, financial literacy has the most dominant impact, indicating that MSME actors with higher financial knowledge are more capable of managing budgets, controlling cash flow, and making sound financial decisions. The model explains 43.1% of the variance in financial management, confirming the relevance of these two variables. These results highlight the importance of improving financial education and encouraging systematic accounting practices to enhance the sustainability and competitiveness of MSMEs.